2008
DOI: 10.1162/pres.17.6.550
|View full text |Cite
|
Sign up to set email alerts
|

A Fingertip Haptic Display for Improving Curvature Discrimination

Abstract: This paper presents a novel haptic device providing both kinesthetic and cutaneous cues informative of shape geometry at the contact point. The system is composed of a supporting kinesthetic haptic interface and an innovative fingertip haptic display that can instantaneously orient a small plate along the tangent plane at the contact point with a virtual shape and bring it in contact with the fingertip. We show how this local augmentation of displayed haptic information can improve human performance in shape e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 21 publications
1
49
1
1
Order By: Relevance
“…One of these studies has also investigated providing tactile feedback from a pin array in combination with kinesthetic feedback [7]. Other interesting approaches to tactile/kinesthetic display include research on displaying the local object surface tangent [4,6]. Dostmohamed and Hayward present a device that utilizes a gimballed plate to represent the local surface tangent plane of virtual objects.…”
Section: Combined Tactile and Kinesthetic Feedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these studies has also investigated providing tactile feedback from a pin array in combination with kinesthetic feedback [7]. Other interesting approaches to tactile/kinesthetic display include research on displaying the local object surface tangent [4,6]. Dostmohamed and Hayward present a device that utilizes a gimballed plate to represent the local surface tangent plane of virtual objects.…”
Section: Combined Tactile and Kinesthetic Feedbackmentioning
confidence: 99%
“…The motion of the gimballed plate is coordinated with the user's kinesthetic motions to display curved objects [4]. As a relatively sophisticated adaptation of the work by Dostmohamed and Hayward, Frisoli et al present a miniaturized finger-based tilting plate tactile display that can be attached to a kinesthetic display [6]. Finally, the author's prior studies have shown the potential of contact location feedback for enhancing object curvature and motion cues [15].…”
Section: Combined Tactile and Kinesthetic Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…of Siena, Italy. {meli, salviettigio, prattichizzo}@diism.unisi.it 2 Pacchierotti is with CNRS, Univ Rennes, Inria, IRISA, Rennes, France.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a tactile display with large tactile surfaces having spatial resolution is needed for object recognition. However, it is very difficult to produce a composite presentation device combining tactile sensation and force since no tactile displays that capable of satisfying these requirements simultaneously has been developed for practical use, in spite of the many attempts [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%